Characterization and analysis of AlGaN/GaN HEMTs on Si for high frequency application - Pang, Vanessa Du Juan (2017)
AlGaN/GaN HEMTs are perfect candidates for high-frequency, high-voltage and high-power applications such as radar and wireless communication systems, DC-DC convertors, as well as cellular base stations. Intrinsic material parameters, which will be further elaborated in the report, allow it to be efficient under extreme conditions. It forms a 2D electron gas channel at the AlGaN/GaN heterojunction interface, which results in high carrier mobility, causing GaN HEMTs to be an agile and versatile device [01]. The electrical characterisation technique is used to characterise GaN HEMTs within this report. The utilisation of GaN components is developing readily in military radar and electronic warfare system designs as an alternative or substitution for laterally diffused MOSFET components. Also, GaN is the latest RF and microwave semiconductor technology in the market, and its characteristics and requirements are distinctive from the others [02]. Presently, due to the material’s desirable characteristics, there have been many advances made in these areas. However, reports have also discussed various current collapse mechanisms of the field effect transistors through trap-related phenomenon, source and drain resistances. These issues have not been solved and the root causes are yet to be determined; thus the device is still not able to meet the production quality for adoption into major RF power applications. Therefore, detailed studies and experiments have to be conducted to identify and understand issues with the material, and through research, finding the better way to optimise the AlGaN/GaN HEMTs for high frequency applications, bringing us closer to materialising commercially large-scale fabrication of GaN HEMTs. Thus this report of AlGaN/GaN HEMTs on Si substrates will introduce the fundamental properties of the HEMTs, by showing the methods of characterisation, analysis and optimisation for high frequency applications in light of technological advancements in order to bring us a step closer to materialising commercially large- scale fabrication of GaN HEMTs.